2013
DOI: 10.1016/j.jaci.2012.12.1351
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulatory Effects of IL-22 On Allergen-Induced Pulmonary Inflammation

Abstract: IL-22 is a Th17/Th22 cytokine that is increased in asthma. However, recent animal studies showed controversial findings in the effects of IL-22 in allergic asthma. To determine the role of IL-22 in ovalbumin-induced allergic inflammation we generated inducible lung-specific IL-22 transgenic mice. Transgenic IL-22 expression and signaling activity in the lung were determined. Ovalbumin (OVA)-induced pulmonary inflammation, immune responses, and airway hyperresponsiveness (AHR) were examined and compared between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…YBronchial hypersensitivity Taube et al, 2011 [22] Fang et al, 2014 [21] Besnard et al, 2011 [18] In vivo, with mice challenged with ovalbumin In vivo, with mice challenged with ovalbumin In vivo, with mice challenged with ovalbumin (after addition of exogenous recombinant IL-22 during the antigen challenge) YIL- 33 YInduction of the differentiation of IL-5+ IL-4À CD4+ Th cells Y YEosinophilic inflammation Besnard et al, 2011 [18] In vivo, with mice challenged with ovalbumin (after addition of exogenous recombinant IL-22 during the antigen challenge)…”
Section: Anti-inflammatory Effect Of Il-22mentioning
confidence: 99%
See 1 more Smart Citation
“…YBronchial hypersensitivity Taube et al, 2011 [22] Fang et al, 2014 [21] Besnard et al, 2011 [18] In vivo, with mice challenged with ovalbumin In vivo, with mice challenged with ovalbumin In vivo, with mice challenged with ovalbumin (after addition of exogenous recombinant IL-22 during the antigen challenge) YIL- 33 YInduction of the differentiation of IL-5+ IL-4À CD4+ Th cells Y YEosinophilic inflammation Besnard et al, 2011 [18] In vivo, with mice challenged with ovalbumin (after addition of exogenous recombinant IL-22 during the antigen challenge)…”
Section: Anti-inflammatory Effect Of Il-22mentioning
confidence: 99%
“…Recent studies involving experimental animal models have shown results contradicting those reported previously; Th22 and IL-22 have an anti-inflammatory effect in airway inflammation. 21,22 Some studies using animals reported that IL-22-positive mice had a reduced number of eosinophils and a lower level of IL-13 (which usually increases bronchial hypersensitivity) in the bronchoalveolar lavage and mucus-producing cells in the airways after ovalbumin stimulation when compared with IL-22-negative mice. 21,22,38 Moreover, an in vitro study with bronchial epithelial cells from healthy and asthmatic subjects revealed that IL-22 might inhibit the IFN-gamma-induced expression of CD54 (intercellular adhesion molecule 1, which plays an important role in T cell migration and recruitment), and chemokines CCL5 (chemoattractant for eosinophils, T lymphocytes, and monocytes) and CXCL10 (important for the recruitment of lymphocytes).…”
Section: Anti-inflammatory Effect Of Th22 In Allergic Airway Diseasesmentioning
confidence: 99%
“…Some evidence suggests that IL-22 acts as a proinflammatory cytokine, but others pointed to an opposite function. 66,67 These discrepancies may be due to the difference in the study methods and the time-points to block or exaggerate IL-22 expression in murine models. 66,67 For example, allergic lung inflam- Dermatophagoides pteronyssinus and Dermatophagoides farinae.…”
Section: Nk Cells Represent the Prototypical Member Of Ilc Family Andmentioning
confidence: 99%
“…66,67 These discrepancies may be due to the difference in the study methods and the time-points to block or exaggerate IL-22 expression in murine models. 66,67 For example, allergic lung inflam- Dermatophagoides pteronyssinus and Dermatophagoides farinae. 73 However, whether up-regulated IL-22 has a pathogenic role or functions as a negative feedback mechanism to control inflammation in AR requires future investigations.…”
Section: Nk Cells Represent the Prototypical Member Of Ilc Family Andmentioning
confidence: 99%
See 1 more Smart Citation